Electrochemical behaviour of cationic polyelectrolytes at a polarized liquid/liquid interface - Riva, Julieta Soledad (2014)
The behaviours of several cationic polyelectrolytes (chitosan; polyquaternium-4; diethylaminoethyl dextran; polyquaternium-10, and aminoacrylmethacrylate copolymer, Eudragit® E100) at a polarised liquid/liquid interface are analysed and compared in the present paper. Based on the analysis of the voltammetric results, it was possible to determine some of the relationships between polymer structure and the tendency to adsorb at the interface. It was also possible to determine the substitution degree of a polymer comprising a chitosan main chain modified with glycidyltrimethylammonium chloride, and the values obtained are in agreement with those calculated using other methodologies. Finally, we report a comparative study concerning the effect of cationic (chitosan) and anionic (dextran sulphate) polyelectrolytes on the compactness of a phospholipid film.